Pelatihan Etika Berbahasa di Media Sosial bagi Siswa Kelas X SMK Yapim Bandar - Tansliova, Lili; Marini, Netti; Resmi, Resmi; Turnip, Berlian Romanus; Nasution, Tuti Ariani; Saragih, Rosmeri (LPPM Univ. Ibn Khaldun Bogor, 2022)
At this time, science and technology are developing rapidly. Where humans really need social media in their lives both to get the latest information or other things. The use of social media is increasing every year. Daily human activities cannot be separated from the use of social media. However, users sometimes do not understand good language etiquette in using social media. This will have a negative impact or effect on the social media users themselves or other users. The partners for this community service activity are the Yapim Bandar Vocational School, precisely in class X. This community service activity is carried out for four months, starting from May to September 2021. The mass media users, both Facebook, Instagram, and other part. Where their previous habit was when using social media, they did not pay attention to ethics in language so that it could lead to misconceptions with readers or other social media users. It is hoped that with the training held by the community service team, in the future, class X SMK Yapim Bandar students can use language ethics when using mass media